Mea maxima culpa [videorecording (DVD)] : silence in the house of God - Gibney, Alex; Gibney, Alex
Investigates the secret crimes of Father Lawrence Murphy, a Milwaukee priest who abused more than 200 deaf children in a school under his control. The film documents the first known public protest against the pontiff himself. The investigation helped uncover documents from the secret Vatican archives that show the Pope, who must operate within the mysterious rules of the Roman Curia, as both responsible and helpless in the face of evil.